2004
DOI: 10.1557/proc-820-o8.17
|View full text |Cite
|
Sign up to set email alerts
|

A study of the growth curves of C. xerosis and E. coli Bacteria in Mediums Containing Cobalt Ferrite Nanoparticles

Abstract: Previous publications demonstrated the sensibility of the bacteria, when these were reproduced in mediums that contain nanoparticles of luminescent silicon. The mentioned effect takes place in the development of a bacteriological sensor. The present investigation is centered on the study of the growth curves of E. coli and C. xerosis, but now in the presence of nanosize particles of Cobalt Ferrite (CoFe2O4) which were produced by the co-precipitation method in a watery phase. These nanoparticles present ferrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…These nanoparticles exhibit magnetic properties that might interact with the electric polarity of the bacteria and influence its growth [8].…”
Section: Advantages Of Spionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nanoparticles exhibit magnetic properties that might interact with the electric polarity of the bacteria and influence its growth [8].…”
Section: Advantages Of Spionmentioning
confidence: 99%
“…There are varied nanoparticles that enhance growth cycle, mechanical and physiochemical stability along with biodegradability. The cobalt-ferrite nanoparticles have reported to enhance the growth of Escherichia coli and Corynebacteriumxerosis [8].Nanometric silicon particles have also reported that it alter the growth profiles of bacteria [9]. Several inorganic nanoparticles, including silica, silica/iron oxide, and gold have been shown to exhibit no negative influence on the growth and activity of E. coli [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle cobalt-ferrite have reported to enhance the growth of Escherichia coli and Corynebacterium xerosis (Flores et al, 2004). Nanometric silicon particles have also reported that it accelerate the growth profiles of bacteria (Pérez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among a variety of ferrite based Nano-forms, recently SPION have broad applications in several fields including magnetic fluids, magnetic drug delivery, microwave devices and high-density information storage. These SPION exhibit magnetic properties that might to interact with the electric polarity of the bacteria and influence its growth (Flores et al, 2004). …”
Section: Introductionmentioning
confidence: 99%